Pattern recognition and computer vision : second Chinese Conference, PRCV 2019, Xi'an, China, November 8-11, 2019, Proceedings.: second Chinese Conference, PRCV 2019, Xi'an, China, November 8-11, 2019, Proceedings. Part II (2019) - Unknown
No abstract available